‘Blackness’ is a key site through which surveillance is practiced, narrated and enacted. In short, as S. Browne puts it: ‘Surveillance is nothing new to black folks. It is the fact of antiblackness’. - Kapourelakou, Niki (Kent Law Review, 2022)
“We were hemmed in upon every side”.[1] This statement by Frederick Douglass, although short and concise, powerfully conveys the implications of being constantly overlooked and observed, with no ability of escaping other's gaze, a process familiar in the lives of black slaves. An absence of privacy is what one recognizes as the effect of being interminably watched from every corner, with different methods of surveillance used to strip the observed from their rights, including what Simone Browne describes as 'racializing surveillance'.[2] Racializing surveillance is defined as an exercise of social control enacted through methods of surveillance practices and techniques that allow for the “power to define what is in or out of place”.[3] This suggests an interpretation of surveillance as the act of defining what constitute social norms based on race, whilst giving the watcher the ability to control another’s social standing. Racializing surveillance involves strategies of observation and tracking used by the privileged white society during postcolonialism and the transatlantic slave trade; strategies which privilege the white man while conducting discriminatory treatment against those being racialized.[4] Although many understand surveillance as a phenomenon of contemporary technological advances, and as providing protection against criminal behaviour, what many do not understand is that its enactment can be tracked back to the emergence of slavery. One needs to consider the techniques used for controlling the lives of black societies in earlier epochs, in order to recognize the relationships and similarities between those and the surveillance methods we are familiar with, whilst also understanding their long-lasting effects of racializing surveillance.[5] This paper will argue that surveillance is not a contemporary aspect of society enacted through technological advances, but rather stems from an era of slave trade and postcolonialism that targeted black peoples, and enforced methods to control their social standing by taking away their rights. Browne’s ‘racializing surveillance’ can be explored in depth by looking at ways in which black slaves were treated as property white slaveholders were entitled to, an aspect found in the methods of tracking through runaway advertisements, biometric surveillance techniques such as branding, and the introduction of the Book of Negroes. Other surveillance methods, enacted for social control included constant observation using the elements of space and light, creating a depiction of black criminalisation partnered with suspicious behaviour, one that has since evolved into gratuitous racial profiling. In addition, this essay will explore relationships between methods used during postcolonialism and the transatlantic slave trade, and the surveillance techniques apparent today such as CCTV, passports, and fingerprint scanning. Tracing back to black slavery, the entities of light and space, as well as their interconnection, were predominantly used in creating systematic racialized surveillance. Light and space were used in architecture to enforce the power of the sovereign by creating discipline through observation. In 1786, the Panopticon was conceived by Jeremy Bentham, transferring the idea of discipline into a tangible being; a circular prison with an observation tower standing in the centre.[6] The central concept of this architectural design was viewpoints and sight, the ‘inspector’s’ process of watching all.[7] Foucault interpreted the Panopticon as an act of disciplinary surveillance, with the focus falling upon the prisoners and their inability of knowing whether at any specific time they are being watched. Surveillance in the Panopticon can be discerned through its use of space. The prison cells placed on the circumference of the building meant that the observation tower could see all at every moment. Nothing could be done around the prison that would not be witnessed by the inspector. Cells were also built using methods which minimized communication between the prisoners. Small lamps were placed on each of the tower’s windows during night-time, so that the security apparent in the day could be extended to the night, creating an inability of knowing whether one is being watched or not at any given time, due to the blinding light. There were rules and strict timetables prisoners had to follow to avoid punishment. These factors, took away the prisoner’s rights and privacy, and allowed 'the sovereign' to force discipline and self-surveillance upon its subjects. It is important to recognize the argument that Foucault’s interpretation of the Panopticon is not necessarily what Bentham intended. Bentham’s implications of liberalism within its design suggests this distinction from Foucault’s understanding and theory, as he aimed to free prisoners from coercion (in the form of violence) within the prison, whilst giving a certain autonomy to the prisons’ administration by disallowing superiors from commenting on a prison’s performance.[8] This provides an argument against the idea that surveillance was used throughout history to limit the power of people while handing superiority to the sovereign. Having said this, Foucault’s interpretation holds importance in conveying that this design did in fact create an all-seeing sovereign through the central observation tower, and therefore a power-relationship whereby space and light were used to strip prisoners of their rights, provide the sovereign with the power, and the prisoners with discipline and self-surveillance. It is important to consider the parallels apparent between self-surveillance due to an all-knowing sovereign within the Panopticon, and the present widespread use of CCTV and surveillance cameras that forces discipline upon all who have knowledge of their existence.[9] Furthermore, Bentham’s Panopticon has evolved into the now panoptic society constantly watched through CCTV and via data gathered through technological tracking; examples supporting Foucault’s explanation of the observer holding disciplinary power over the one being watched.[10] Thus the surveillance people are now familiar with, stems from methods of surveillance holding connotations of power. The use of light in enforcing discipline can also be seen in a different form of racialized surveillance, one that criminalized black people and punished them for not complying. The New York Lantern Laws were enforced in the 18th Century, carrying similar connotations to the Panopticon, where light was seemingly used to allow for the security found in the day to be carried into the night. These 1731 laws stated that unattended black, mulatto and Indian slaves of over fourteen years of age, when walking in New York after dark, were obliged to hold lit lanterns in order to be easily detected.[11] If a slave was found without one, they were sentenced to a public whipping. Such laws were passed in order to allow “the black body to be constantly illuminated”[12] from day to night, so that their location was always known and their ability of escape, diminished. These laws gave the power of an all-knowing sovereign to the observer.[13] They also marked all black people as a security risk to the rest of the community, consistently criminalised and in need of supervision both in light and darkness. This process of criminalisation is comparable to the present use of CCTV cameras.[14] Whoever enters a shop, for example, is criminalised and seen as being at risk of committing theft or other criminal actions. Such surveillance and criminalisation can be seen to have developed from laws of surveillance directed at black people. This problematic concept of racialized surveillance, and specifically of the New York Lantern Laws, can be summarized by the following quotation from Browne’s Dark Matters, which refers to a letter by an unnamed author published within the New York Journal and State Gazette, which questioned ‘a law that allowed “a white drunkard” to “disturb the street til midnight, with impunity; when a poor black girl of fifteen if a gale of wind unfortunately extinguishes the candle in the lanthorn, is hurried to gaol, and next morning ignominiously scourged in public.”’[15] This method of surveillance did not simply criminalize black people, it also categorized non-whites as less than ‘human’ based on the their being referenced as property of the slave owners, and as property that needed monitoring.[16] Thus surveillance arose in the context of ‘antiblackness’, and was practiced through ‘blackness’. Indeed, with the Lantern Laws white people were obliged to stop black people who did not have lit lanterns after dark; reflecting the contemporary act of stop-and-search policing.[17] Similarly, the policing method of Omnipresence, which is the use of strong lights to illuminate housing or people, and coupled with an abundance of policing and lights in specific areas, parallel the Lantern Laws' subjection of people to a play of light.[18] When one becomes aware of the possibility of being consistently watched through surveillance at any given moment, a “performative sensibility”[19] arises, as Richard Iton suggests. Where there is an expectation of being watched from the observation tower In the Panopticon, for example, with the tower illuminated at night so that prisoners do not know whether they are actually being observed, a pressure to be on their best behaviour arises. The same can be said of the lanterns, with the fear of being caught and whipped governing behaviour whether or not under observation. This performative sensibility is illustrated in Frederick Douglass’s experience of the overseers during his time on a plantation, where Covey, his overseer, undertook a method of surprise.[20] He would appear at unknown times, and know of the slaves’ actions. So, this coupled with the fear of punishment allowed him to be everywhere at once.[21] Slaves, therefore 'self-surveilled' themselves in fear of being caught. The contemporary mass use of CCTV can be understood in the same way. Although this system created a form of racialized surveillance and criminalisation, there was actually great resistance in the forms of ethnic tradition and art.[22] Using Iton’s Idea of “visual surplus”, it can be seen that performing freedom during slave escapes and expressive art were paired with performative sensibility based on acting in certain ways without the knowledge of when they were being watched. These were acts of refusing to be recognized as less than human and as the white's property.[23] Foucault’s theory of power and knowledge classifies the regulation of society, and more specifically of black populations, as a practice of disciplinary power through surveillance.[24] He argues that a new power relationship is created through surveillance, in which observation and discipline play an integral part. The finalization of torture as a public spectacle marks the beginning of this new power relationship, interlinked with racialized surveillance and rising from Foucault’s view that knowledge is power.[25] The shift from public torture to the prison system modified the exercise of power from having a hold on the body to having a hold on the soul.[26] This comes from stripping people of their rights, in forms such as obligations and prohibitions rather than physical pain, including imprisonment, deportation, strict timetables and obligatory labour. In the prison system within the Panopticon, for example, prisoners are confined in cells, are bound by rules, strict timetables that could not be avoided, and the constant overlooking through the observation tower.[27] The observers and the sovereign can constantly gather knowledge of the prisoners, with the latter self-surveilling themselves due to their inability to know if they are being watched. Achille Mbembe argued that constant watchful eyes over black people and their forceful acceptance of a strict timetable not only takes away the peoples’ rights, but also acts as a form of punishment[28] that, as Foucault argued, can go beyond the body. As Foucault analysed, the one who holds the knowledge holds the power, creating a systematic control over prisoners.[29] He also suggested that knowledge can arise from power, so that the white sovereign given the power of watching gains knowledge that can be further used to control the black population.[30] A disciplinary situation therefore arises from this relationship, by which the surveilled acknowledges their lack of power in this relationship and the sovereign’s ability to practice control. The power relationship existing in the act of surveillance leads to what is referred to as ‘dark sousveillance’ and counter-surveillance. In slavery, dark sousveillance was used to allow one to be out of sight, allowing for a flight to freedom, while confronting the methods used on slaves.[31] The Underground Railroad was an achievement of black sousveillance that allowed slaves to escape surveillance.[32] Now, it can take the form of filming from mobile devices during encounters with the police. As Douglass stated, even if a hundred people witnessed the murder of a man, their word alone would not be acknowledged.[33] Anti-surveillance tactics, including singing to warn off observers, were used to avoid watching eyes, suggesting that the surveillance methods used for controlling slaves were not adequate in making them obliging.[34] Technologies used for surveillance, more specifically racialized surveillance, instituted through the period of slavery to track blackness as ‘property’ were also articulated through the act and narratives of slave escapes. They are found in the reasoning behind passports and other national identification, which can be tracked back to black slavery, where the white ‘owners’ enacted methods of surveillance to track down runaways. These forms of surveillance monitor where an individual is at a specific point in time and can control one’s ability to move from one place to the next. Nowadays, this takes the forms of passports and identification requirements, as well as newfound tracking technologies on mobile phones and other devices. Historically, this tracking surveillance was enacted in the form of the Book of Negroes, formulated as a public record of black people in North America, which allowed slaveholders to track down their property that attempted to escape.[35] It was the first document of migration surveillance enacted by the government, and like passports, stated whether one had the right of travelling, whilst making one easily identifiable.[36] This record held information such as a physical description, a date of birth, as well as the name of the black slave and their claimant or master they were owned by. Due to attempted escapes during the British evacuation, Birch Certificates were given to those permitted to travel, and those granted ‘freedom’.[37] These certificates acted as de facto passports.[38] Thus was the introduction of surveillance through passports a racialized process. The relationship between passports and The Book of Negroes is easily recognised as a record for treating black slaves as property rightfully owned by a white slaveowner, as well as defining the extent of control black people had over their own bodies. Indeed, the surveillance of slaves was further epitomised through branding of slaves’ bodies to allow for easy identification. When looking at the relationship between current surveillance methods and the surveillance of black slaves, it is important to recognise the methods used to track and control black people in earlier years, treating them as property. Objectified ways of treating black slaves included treaties that stated during British evacuation, “carrying away Negroes” or “other Property of the American inhabitants” was not permitted, and where it was found that the British did in fact do so, slaveowners were compensated for their loss of property.[39] Due to Art.7 of a provisional peace treaty, inspections were performed on ships, whereby masters could repossess their property – the slaves.[40] These examples illustrate the objectification of black people during this period. Others include the use of the census and runaway advertisements. The census was a way of categorizing populations and allowing them to be made legible and easily trackable based on race and gender.[41] Similarly, the runaway advertisements used to track down runaway slaves included stereotypical racial profiling, physical description and unique features, and descriptions of the slaves’ suspicious behaviour.[42] Obtaining social control through the practice of biometric surveillance has remained abundantly familiar to people involved in the present time of immigration. During black slavery, the biometric surveillance slaves were exposed to, created a prototypical basis for the biometric surveillance people experience in the contemporary world.[43] During the transatlantic slave trade, slaves were marked and scarred in particular ways that could either confirm their status as a slaveholder’s property and part of a plantation, or aid in tracking them in case they tried to escape.[44] Whipping was a method abundantly used as a form of punishment, which surveilled slaves and instilled fear within the plantation to keep them from disobeying their owners or trying to run away.[45] Furthermore, some were marked with a branding iron so that they were easily locatable in case of escape.[46] Another method of aimed at preventing slaves from running away from their plantations was the impregnation of female slaves, which physically and emotionally tied the women slaves to their plantation, more so when in 1662 it was codified into law that children born of women slaves were the property of the mother’s slaveholder.[47] One can find also see a connection between the biometric surveillance of branding, and the contemporary use of fingerprint scanning,[48] both policing methods the latter now exercised through mobile devices. Fanon defined epidermalization as the process of assigning certain meanings to specific races or bodies.[49] The Western population used this as a disassociation between the black race and the rest of the world, conveying the black body as a black object capable of being defined by them[50], creating a hierarchy of knowledge obtained by the two.[51] The black body was then able to be treated in specific ways based on colour and characteristics, comparable to the different treatment given to white people, something established during the transatlantic slave trade.[52] A connection can be formed between epidermalization and contemporary forms of biometric surveillance, such as e-passport verifications, that digitally produce the ‘truth’ of one’s body. There is an evident relationship between biometric surveillance used during black slavery and in the contemporary era of immigration, both consistent with the mapping of the colonized body by the colonizer, and the branding of the black slave body.[53] States have responded to the issue of dispossession and foreign arrivals by using surveillance methods to practice control over these people, and either imprison them or try to prevent them from entering the country. For example, those entering European countries from Afghanistan are faced with the rejection of their asylum claims and given contradictory reasoning for this.[54] So, when an individual is above the age of eighteen, they are no longer an unaccompanied adult, and the state does not have an obligation to provide asylum. In an article based on Danish response to immigrants, it is argued that when doctors conduct examinations on the immigrants to establish their age, most cases are found to be over the age of eighteen, even though the individuals are aware of their age and claim to be younger than that.[55] An example of approach is the case of twin boys who were deemed to have different ages.[56] Through tests, several physical aspects are noted down, suggesting that these ‘special characteristics’ found can be used for biometric surveillance, similarly to the methods used on black slaves.[57] Again, it is important to understand the similarity of the colonisers or slaveholders mapping the bodies of the colonized or slaves, with the data collection apparent in these examinations made on people seeking asylum. During one interview conducted on an individual seeking asylum, it was mentioned that their experience with the doctors included scarce conversation, with a translator instructing them on what to do being the only thing said.[58] This can be linked with the briefness of doctor-patient relationships in colonial contexts, where doctors did not indulge in questioning the patient but rather conducted examinations they could use to control the subject, as well as mapping the colonized bodies[59] in order to gain knowledge that could give them power over them.[60] In finding further links between the enactment of surveillance in controlling people of a certain race, and the use of surveillance now, Francis Galton expresses that fingerprints need to be considered.[61] Fingerprints have been used widely in categorizing populations of certain races, and the increase of fingerprint use in the contemporary reenforces the closeness of surveillance methods that were introduced for issues of controlling race. Racial profiling is an issue talked about copiously in the present day, creating issues of stereotypical racism. Although voiced as a contemporary issue, racial profiling occurred throughout history. 'Prototypical whiteness' is a phrase that encompasses the Western ideology of white superiority and civilization, while fabricating the society of black people as exhibiting particular characteristics, such as being uncivilized, that allows such stereotypes to underpin forms of racializing surveillance both past and present.[62] Thus, during the postcolonial period, the Western ideology continued to present black people as unruly and a potential threat to the rest, and therefore in need of constant repression and surveillance in order to maintain social control.[63] A false identity is therefore given to black people that mirrors the white person’s portrayal of stereotypical characteristics that identify them as lesser beings. As Gilroy expressed, “identity forever sets one group apart from others who lack the particular, chosen traits that become the basis of typology and comparative evaluation.”[64] This quotation encompasses the idea that identity given to black people by the Western sovereign separates them from the white society, a branding that remains through time and form the basis of racial profiling. These imposed stereotypes black can be clearly seen through runaway advertisements during black slave escapes, and their slaveholders’ attempts of finding their ‘property’ through such surveillance methods. Runaway advertisements were widely used as a tracking method by slaveowners to help locals to find them. These advertisements described physical characteristics, as well as other attributes that could help locate them.[65] Stereotypical descriptions were abundant in such advertisements, with descriptions including bad behaviour, rolling eyes whilst talked to, and not knowing their place. This Is echoed in Adrian Piper’s video What It’s Like, What It Is, where a man is heard to be refusing the acceptance of stereotypes given to him, saying “I’m not pushy. I’m not sneaky. I’m not lazy. I’m not noise”, “I’m not vulgar. I’m not rowdy. I’m not horny. I’m not scary.” Such stereotyping of black people, used to excuse the racializing surveillance forced upon them, are still present today. Through it, black styling and ethnic expression are criminalized and seen as ‘uncivilized’, and even included clothing articles such as baggy pants, which were actually made illegal under the Negro Act 1735. This criminalization based on clothing and looks can be linked to stop-and-frisk policing methods, where the justification is made on the grounds of the person ‘looking suspicious’ airports. In accordance with racial profiling and racialized surveillance, it is important to understand contemporary examples of stereotypical, racial surveillance. According to UK statistics from 2018[66], black people were 53% more likely to be incarcerated from the crown court than white people. Also, black men were 56% more likely to be held in custody, with 60% pleading not guilty. In the United States, black men of twenty to twenty-four years of age are imprisoned at rates seven times higher than the likelihood of white men being incarcerated between that age.[67] These figures suggest that there is still, in fact, stereotypical racism when it comes to imprisoning people, suggesting that it acts as a form of racialized surveillance due to imprisoning black people in order to obtain control over them. In conclusion, although surveillance is usually thought of as an aspect of society present in the contemporary era and arising from new technological advances, it can be convincingly argued that it was in fact enacted for and practiced through the times of black slavery. Browne's concept of ‘racializing surveillance’ creates a lens through which one can discern the methods of surveillance that were used to uphold control over the black population by the white sovereign, and through which the black person was treated as property to be disciplined into compliance through constant observation and fear of punishment. Surveillance methods such as the use of space and light, as well as advertisements and de facto passports, allowed the sovereign to obtain consistent knowledge of the black slaves and their location, and, as theorized by Foucault, knowledge through watching is power given to the observer. It is important to acknowledge the foundations of surveillance apparent today, as stemming through racialized surveillance formed to control black society and undermine their rights and, therefore, their lives - essentially defining them as white property. The relationship between the Panopticon, and its use of space, and the contemporary use of CCTV’s is apparent, with the self-surveillance that arises out of both. Another example are the parallels between the Lantern Laws and stop-and-frisk policing of suspicious individuals. Similarly, under biometric surveillance, the mapping of the colonised body and branding of black slaves can be reflected in the notetaking of immigrants’ ‘special characteristics’, and the Book of Negroes and the associated de facto passports, provide a foundation for modern passports and other forms of identification that allow us to travel. We can therefore conclude that racialized surveillance, seen through the lens of history, is not only closely linked to the surveillance methods we are accustomed to today, but also still practiced for the controlling of the black population, and this fact both largely and negligently ignored. Bibliography Articles Damien Riggs, 'How Do Bodies Matter? Understanding Embodied Racialised Subjectivities | Darkmatter Journal' (Darkmatter101.org, 2008) <http://www.darkmatter101.org/site/2008/02/23/how-do-bodies-matter-understanding-embodied-racialised-subjectivities/> accessed 11 March 2021. David Lyon, Kirstie Ball and Kevin Haggerty, Routledge Handbook Of Surveillance Studies (2012), 21-25 Jessa Lingel, 'Review Of Dark Matters: On The Surveillance Of Blackness By Simone Browne' Maša Galič, Tjerk Timan and Bert-Jaap Koops, 'Bentham, Deleuze And Beyond: An Overview Of Surveillance Theories From The Panopticon To Participation' (2016) 30 Philosophy & Technology. Mbembe A, 'Necropolitics' (2003) 15 Public Culture, 11-40. Moya K. Mason, 'Foucault And His Panopticon - Power, Knowledge, Jeremy Bentham, Surveillance, Smart Mobs, Protests, Cooperation, Philosopher' (Moyak.com, 2021) <http://www.moyak.com/papers/michel-foucault-power.html> accessed 12 March 2021. Sara Cullen, '“Let Him Be Left To Feel His Way In The Dark;” Frederick Douglass: White Surveillance And Dark Sousveillance' [2018] Surveillance, Race, Culture. Books Douglass F, Life and Times Of Frederick Douglass (1881) Foucault M, Discipline and Punish: The Birth Of The Prison (1975) Frantz Fanon, Black Skin, White Masks (1967) Paul Gilroy, Between Camps: Nations, Cultures And The Allure Of Race (1st edn, 2004), 104 Simone Browne, Dark Matters: On The Surveillance Of Blackness (2015) Simone Browne, Race And Surveillance (2012) Interviews Claudia Garcia-Rojas, Interview with Simone Browne, 'The Surveillance Of Blackness: From The Trans-Atlantic Slave Trade To Contemporary Surveillance Technologies' (2016). Websites Alana Lentin, 'Black Sousveillance Against ‘Prototypical Whiteness’: Thinking With Simone Browne' (Alana lentin.net, 2017) <https://www.alanalentin.net/2017/04/06/black-sousveillance-against-prototypical-whiteness-thinking-with-simone-browne/> accessed 12 March 2021. Ministry of Justice, 'Statistics on Race and The Criminal Justice System 2018' (2018). [1] Douglass F, Life And Times Of Frederick Douglass (1881) [2] Simone Browne, Dark Matters: On The Surveillance Of Blackness (2015), 16-18. [3] Ibid, 16. [4] Ibid, 17. [5] Ibid, 16-18. [6] David Lyon, Kirstie Ball and Kevin Haggerty, Routledge Handbook Of Surveillance Studies (2012), 21-25 [7] Ibid. [8] Ibid. [9] Maša Galič, Tjerk Timan and Bert-Jaap Koops, 'Bentham, Deleuze And Beyond: An Overview Of Surveillance Theories From The Panopticon To Participation' (2016) 30 Philosophy & Technology. [10] Ibid. [11] Browne, Dark Matters, (n2),78-79. [12] Ibid, 79. [13] Ibid. [14] Galič, Timan and Koops, 'Bentham, Deleuze And Beyond’, (n9) [15] Browne, Dark Matters, (n2), 80. [16] Jessa Lingel, 'Review of Dark Matters: On The Surveillance Of Blackness By Simone Browne', 3 [17] Claudia Garcia-Rojas, Interview with Simone Browne, 'The Surveillance Of Blackness: From The Trans-Atlantic Slave Trade To Contemporary Surveillance Technologies' (2016). [18] Ibid. [19] Browne, Dark Matters, (n2),76-77. [20] Douglass, Life And Times Of Frederick Douglass, (n1). [21] Ibid. [22] Browne, Dark Matters, (n2), 77. [23] Ibid. [24] Foucault M, Discipline And Punish: The Birth Of The Prison (1975) [25] Ibid. [26] Ibid. [27] Ibid. [28] Mbembe A, 'Necropolitics' (2003) 15 Public Culture, 11-40. [29] Moya K. Mason, 'Foucault And His Panopticon - Power, Knowledge, Jeremy Bentham, Surveillance, Smart Mobs, Protests, Cooperation, Philosopher' (Moyak.com, 2021) <http://www.moyak.com/papers/michel-foucault-power.html> accessed 12 March 2021. [30] Ibid. [31] Sara Cullen, '“Let Him Be Left To Feel His Way In The Dark;” Frederick Douglass: White Surveillance And Dark Sousveillance' [2018] Surveillance, Race, Culture. [32] Ibid. [33] Ibid. [34] Browne, Dark Matters, (n2) [35] Ibid. [36] Ibid. [37] Ibid, 74. [38] Ibid. [39] Ibid, 71-72. [40] Ibid. [41] Ibid, 55-57. [42] Ibid. [43] Cullen, “Let Him Be Left To Feel His Way In The Dark”,(n31) [44] Browne, Dark Matters (n2) [45] Douglass, Life And Times Of Frederick Douglass, (n1) [46] Browne, Dark Matters (n2) [47] Browne, Dark Matters (n2) [48] Ibid. [49] Frantz Fanon, Black Skin, White Masks (1967). [50] Ibid. [51] Damien Riggs, 'How Do Bodies Matter?, (2008) [52] Alana Lentin, 'Black Sousveillance Against ‘Prototypical Whiteness’: Thinking With Simone Browne' (Alana lentin.net, 2017). [53] Nanna Dahler, 'Biometrics As Imperialism: Age Assessments Of Young Asylum Seekers In Denmark' (2020) 62 Race & Class, 24-45. [54] Ibid. [55] Ibid. [56] Ibid. [57] Ibid. [58] Ibid. [59] Ibid. [60] Foucault, Discipline And Punish, (n24) [61] Dahler, 'Biometrics As Imperialism’,(n58) [62] Browne, Dark Matters (n2) [63] Ibid. [64] Paul Gilroy, Between Camps: Nations, Cultures and The Allure Of Race (1st edn, 2004), 104. [65] Browne, Dark Matters, (n2),53-55. [66] Ministry of Justice, 'Statistics on Race And The Criminal Justice System 2018' (2018). [67] Browne, Dark Matters, (n2),13.